2013
DOI: 10.1177/0956462413482424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an educational intervention on knowledge, attitudes and preventive behaviours related to HIV and sexually transmitted infections in female sex workers in southern Iran: a quasi-experimental study

Abstract: This quasi-experimental, before-after study was designed to assess the effect of an educational intervention on knowledge and attitudes about sexually transmitted infections, HIV and preventive behaviours among female sex workers in Shiraz, Iran. A single-group pre-post test design was used and the study was done between August and December 2009. The participants were 80 female sex workers recruited from three drop-in centers in Shiraz, with stratified random sampling. Pre-intervention knowledge was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 16 publications
5
22
0
Order By: Relevance
“…The results of the present study also demonstrate that there was no significant difference between HIV‐infected men and women in terms of mean age in 2009–2014. The results of other studies demonstrated that the mean age of HIV‐infected patients has been decreasing in Iran . The results of studies performed in Bangladesh were also consistent with the results of the present study .…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study also demonstrate that there was no significant difference between HIV‐infected men and women in terms of mean age in 2009–2014. The results of other studies demonstrated that the mean age of HIV‐infected patients has been decreasing in Iran . The results of studies performed in Bangladesh were also consistent with the results of the present study .…”
Section: Discussionsupporting
confidence: 90%
“…In the interventional study of Sakha, there were significant improvements in attitude and the number of participants who reported preventive behaviors such as consistently use of condom (P < 0.001). The results showed that educational program was successful in increasing the participants' HIV- and AIDS-related knowledge and attitudes and decreasing their risky behaviors (23). In a cross-sectional study conducted in 2004 on 100 prisoner men, HIV high-risk behaviors decreased when subjects believed in the effectiveness of strategies designed to reduce the risk or seriousness of impact of the health condition (24).…”
Section: Discussionmentioning
confidence: 99%
“…Iranian harm reduction policy-makers adopted a gradual policy shift from a supply-reduction policy to a revised policy allowing for drug abuse treatment (12). In order to expand the domains of this policy, drop-in centers have been established to strengthen harm reduction programs, particularly for vulnerable women (5,13).…”
Section: Discussionmentioning
confidence: 99%
“…Substance-using women who exchange sex for money, drugs, or shelter are at risk for many health problems arising from non-sterile injecting practices, direct drug effects, and lifestyle factors associated with drug dependence (1,2). They are potential carriers of HIV, and they can transmit HIV to clients and, indirectly, to the general population (5).…”
Section: Introductionmentioning
confidence: 99%